Prognostic value of absolute lymphocyte/monocyte ratio, red cell distribution width and neutrophil/ lymphocyte ratio in diffuse large B-cell lymphoma patients - Hasan, Kawa Muhamedamin; Elmeshhedany, Ahmed Yassin (Cellular and Molecular Biology, 2021)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive and rapid-growing form of non-Hodgkin lymphoma (NHL). The objective of this research was to assess the predictive role of lymphocyte to monocyte ratio (LMR), red cell distribution width (RDW) and neutrophil to lymphocyte ratio (NLR) values in the survival of DLBCL patients. A retrospective analysis of 136 DLBCL patients admitted to Nanakali Hospital for blood diseases and oncology from 2010-2020 was done. We assessed the correlation of LMR, RDW and NLR with patients’ characteristics and the impact on survival by the Kaplan–Meier method, the log-rank test, and Cox regression models for multivariate analysis. The complete remission rate was 61.7%, with a 5- year overall survival (OS) and progression-free survival (PFS) of 59.5% and 60%, respectively. The Log-rank test showed that LMR was significantly correlated with Ann Arbor staging (p= 0.040). There is a significant association between RDW and Eastern Cooperative Oncology Group performance status (ECOG-performance status) (p= 0.022), B symptoms (p= 0.026), Revised International prognostic index (R-IPI) (p= 0.004), lactate dehydrogenase (LDH) (p= 0.021), and beta 2 microglobulin (B2MG) (p= 0.007), whereas NLR had a significant correlation with LDH only (p=0.016). There were no significant differences in the 5-year OS or PFS in patients with different levels of RDW, LMR, and NLR. LMR, RDW and NLR were correlated with many of patients’ characteristics. However, none of the LMR, RDW and NLR did possess value to predict OS and PFS, and they cannot be used as biomarkers for survival evaluation of DLBCL.